Pengaruh CAR, BOPO, FDR dan NPF terhadap Tingkat Profitabilitas pada Bank Muamalat di Indonesia - Arwin Arwin (Institut Agama Islam Negeri Parepare, 2021)
The Influence of CAR, BOPO, FDR and NPF on Profitability at Bank Muamalat in Indonesia. This research was conducted with the aim of knowing the effect of CAR on the profitability of Bank Muamalat in Indonesia, knowing the effect of the BOPO ratio on the profitability of Bank Muamalat in Indonesia, knowing the effect of FDR on the profitability of Bank Muamalat in Indonesia, knowing the effect of NPF on the profitability of Bank Muamalat in Indonesia. This study uses secondary data obtained by documentation techniques in the form of financial reports through the official muamalat website www.muamalat.com. This study uses time series data with a time span of 2000-2015. This study uses a multiple linear regression analysis model using the SPSS 25 program. The results of the research show that partially CAR has a negative and insignificant effect on the profitability of Bank Muamalat. Partially BOPO has a positive and significant effect on the profitability of Bank Muamalat. FDR partially has a positive and insignificant effect on the profitability of Bank Muamalat. NPF partially has a positive and insignificant effect on the profitability of Bank Muamalat.